Tissue-Specific Regulation of Na+ and K+ Transporters Explains Genotypic Differences in Salinity Stress Tolerance in Rice - Liu, Juan; Shabala, Sergey; Shabala, Lana; Zhou, Meixue; Meinke, Holger; Venkataraman, Gayatri; Chen, Zhonghua; Zeng, Fanrong; Zhao, Quanzhi (Frontiers in Plant Science, 2019)
Rice (Oryza sativa) is a staple food that feeds more than half the world population. As rice is highly sensitive to soil salinity, current trends in soil salinization threaten global food security. To better understand the mechanistic basis of salinity tolerance in rice, three contrasting rice cultivars—Reiziq (tolerant), Doongara (moderately tolerant), and Koshihikari (sensitive)—were examined and the differences in operation of key ion transporters mediating ionic homeostasis in these genotypes were evaluated. Tolerant varieties had reduced Na+ translocation from roots to shoots. Electrophysiological and quantitative reverse transcription PCR experiments showed that tolerant genotypes possessed 2-fold higher net Na+ efflux capacity in the root elongation zone. Interestingly, this efflux was only partially mediated by the plasma membrane Na+/H+ antiporter (OsSOS1), suggesting involvement of some other exclusion mechanisms. No significant difference in Na+ exclusion from the mature root zones was found between cultivars, and the transcriptional changes in the salt overly sensitive signaling pathway genes in the elongation zone were not correlated with the genetic variability in salinity tolerance amongst genotypes. The most important hallmark of differential salinity tolerance was in the ability of the plant to retain K+ in both root zones. This trait was conferred by at least three complementary mechanisms: (1) its superior ability to activate H+-ATPase pump operation, both at transcriptional and functional levels; (2) reduced sensitivity of K+ efflux channels to reactive oxygen species; and (3) smaller upregulation in OsGORK and higher upregulation of OsAKT1 in tolerant cultivars in response to salt stress. These traits should be targeted in breeding programs aimed to improve salinity tolerance in commercial rice cultivars.